Congenital superior sternal cleft repair using our modified Sally technique: A case report - Tomoyuki Kuwata; Susam Park; Issei Sakano; Kumiko Kuwata (Elsevier, 2014)
We report the case of an 8-month-old male neonate who underwent reconstructive surgery for a congenital superior sternal cleft to decrease the risk of commotio cordis. With regard to use of the Sally technique for the repair of a relatively wide cleft (4 × 4 cm), we were concerned about respiratory problems caused by compression following closure of the sternal halves. By closing the sternal halves imperfectly, elevation of intrapleural pressure can be avoided to some extent. By bridging the surplus resected cartilage from the lower sternum over the gap of the upper sternum, the heart is protected by more rigid material. We recommend our modified Sally technique because it is both flexible and effective for sternal cleft repair.